2013
DOI: 10.1002/elan.201300285
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and Detection of Hydrogen Peroxide Using δ‐MnO2 Thin Film Electrode with Self‐Healing Property

Abstract: A thin film of δ‐type MnO2 grown cathodically has been investigated with respect to the ability toward anodic decomposition of H2O2 and durability. With polarization at less positive potentials than +0.4 V vs. Ag/AgCl, the film was dissolved exclusively as a result of reduction of Mn4+ sites in the oxide by H2O2 to soluble Mn2+. At +0.9 V, MnO2 remained unchanged and decomposed H2O2 in solution. At +0.8 V, the film was once dissolved in the initial stage; however, it was self‐healed via reoxidation of the libe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…H2O2 is well known to chemically reduce MnO2, even under mild aqueous conditions. [61][62][63] It can thus be assumed that the electrochemically generated H2O2 contributes to the chemical reductive dissolution of the residual MnO2 up to a complete dissolution. Further work is however required to definitely prove such reactivity.…”
Section: Influence Of the Discharging Rate And Charge Transfer Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…H2O2 is well known to chemically reduce MnO2, even under mild aqueous conditions. [61][62][63] It can thus be assumed that the electrochemically generated H2O2 contributes to the chemical reductive dissolution of the residual MnO2 up to a complete dissolution. Further work is however required to definitely prove such reactivity.…”
Section: Influence Of the Discharging Rate And Charge Transfer Resistancementioning
confidence: 99%
“…2, which therefore solely depends on the pH and Mn 2+ activity in solution.In Region II, it is interesting to note that a new potential plateau is reached at  0.65 V, signing a new faradaic process we attribute to the electrochemical reduction of dioxygen into hydrogen peroxide. H 2 O 2 is well known to chemically reduce MnO 2 , even under mild aqueous conditions [61][62][63]. It can thus be assumed that the electrochemically generated H 2 O MnCl 2 , the Mn 2+ concentration locally released in the diffusion layer cannot significantly alter the already high local concentration of Mn 2+ (0.1 M).…”
mentioning
confidence: 99%
“…Porous heterogeneous catalytic structures made of oxides of manganese (Mn O ) are also commonly researched H O catalysts [ 5 , 8 , 39 ]. In the last decade, catalytic structures based on MnO are tested as a compatible active substance of calorimetric H O gas sensors [ 12 , 36 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of different catalysts which have been investigated for the decomposition of H 2 O 2 include noble metal catalysts such as gold nanoparticles supported on KNbO 3 microcubes 9, non‐noble metal compounds such as manganese oxides 10, as well as non‐metal catalysts such as multi‐walled carbon nanotubes 11. Recently, it has been shown that nitrogen doped graphene can catalyse both H 2 O 2 decomposition and reduction reactions 12.…”
Section: Introductionmentioning
confidence: 99%